2012
DOI: 10.2165/11597550-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of a New Anti-Alzheimerʼs Disease Pharmaceutical Composition Combining Memantine and Vitamin D

Abstract: Alzheimer's disease (AD) is the leading cause of dementia. In addition to a decrease in brain cholinergic activity, AD is also marked by glutamatergic excitotoxicity that results in neuronal death, characterized clinically by a loss of learning and memory abilities. The currently available drugs for symptomatic treatment of AD (i.e. memantine and acetylcholinesterase inhibitors) only temporarily slow down the natural history of the disease process. Among them, memantine is the only one that acts as a non-compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 85 publications
2
26
0
2
Order By: Relevance
“…74 Since both AD and PD seem to be caused by abnormal elevations in Ca 2+ , I shall develop the notion that the deleterious effect of vitamin D deficiency may be explained by an alteration in its normal role in regulating intracellular Ca 2+ homeostasis. 75,76 The brain possesses all the enzyme responsible for both vitamin D formation (vitamin D3 25-hydroxylase and 25-hydroxyvitamin D3-1α-hydroxylase) and degradation (vitamin D3 25-hydroxylase). 70,77 Neurons also express the vitamin D receptor (VDR) and VDR polymorphisms have been associated with Parkinson disease, 76 age-related decline in cognition and the incidence of depressive symptoms 78 and is also a risk factor for AD.…”
Section: Alzheimer Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…74 Since both AD and PD seem to be caused by abnormal elevations in Ca 2+ , I shall develop the notion that the deleterious effect of vitamin D deficiency may be explained by an alteration in its normal role in regulating intracellular Ca 2+ homeostasis. 75,76 The brain possesses all the enzyme responsible for both vitamin D formation (vitamin D3 25-hydroxylase and 25-hydroxyvitamin D3-1α-hydroxylase) and degradation (vitamin D3 25-hydroxylase). 70,77 Neurons also express the vitamin D receptor (VDR) and VDR polymorphisms have been associated with Parkinson disease, 76 age-related decline in cognition and the incidence of depressive symptoms 78 and is also a risk factor for AD.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…4). These inhibitory effects of Li + , Bcl-2 of the degenerative processes associated with AD 75 and there is every reason to suspect that it might prove efficacious in other neural diseases such as PD that are driven by a dysregulation of Ca 2+ signaling.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…It slows the progression of mild and moderate-to-severe AD and possibly vascular dementia, though its effects are limited [252]. Memantine acts as a non-competitive low-affinity modulator of NMDA receptors, and results in prevention of neuronal necrosis induced by glutamatergic calcium neurotoxicity, but not neuronal apoptosis resulting from oxidative stress [253]. It blocks excessive NMDA receptor activity, while leaving normal function relatively intact [254].…”
Section: Treatment Strategies For Ad Targeting Slow Excitotoxicitymentioning
confidence: 99%
“…Memantine (MEM) is a derivative of amantadine and has been used to treat a variety of neurological or psychiatric disorders associated with excitotoxic cell death, including Parkinson's disease and vascular dementia [7,8,9]. The therapeutic effect of this compound is due primarily to its ability to bind to N -methyl-D-asparatate (NMDA) receptor-operated cation channels [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that NMDA receptors constitute the main target of MEM, recent studies have shown that it could inhibit ATP-sensitive K + (K ATP ) channels in substantia nigra neurons [12] and suppress electroporation-induced inward currents [13]. MEM has been reported to exert anti-inflammatory actions [7,8,14,15]; however, such mechanisms remain unclear. Additionally, little information is available concerning the mechanisms involved in effect of MEM or structurally similar compounds on Kir channels, while amantidine was reported to block viral K + channels [16].…”
Section: Introductionmentioning
confidence: 99%